MOTIVASI PETANI DALAM MENANAM TANAMAN HORTIKULTURA DI KENAGARIAN SUNGAI NANAM KECAMATAN LEMBAH GUMANTI KABUPATEN SOLOK - -, Rianovita - (STKIP PGRI Sumbar, 2014)
The agricultural sector is one of the focus priority of development in Indonesia because most of the population is still engaged in farming. Development of the agricultural sector aims to increase the yield and quality of production, incomes, living standards of farmers, expandss employment and business opportunities and increase exports. This research aims to describe the motivation of farmers to grow horticulture crops in Kenagarian Sungai Nanam Kecamatan Lembah Gumanti Kabupaten Solok.This research aims to obtain information about : high price, short production time, the processing of which is not too difficult, not too expensive capital to motivate farmers to grow horticulture crops in Kenagarian Sungai Nanam Kecamatan Lembah Gumanti Kabupaten Solok. The research used qualitative method with snowball techniques (snowball sampling). Conducting interviews with horticultural farmers in Sungai Nanam, collecting samples in small numbers at first, then enlarged. Like a snowball rolling into big.From the results of the research is found that a high price, short production time, the management of which is no too difficult, not too expensive capital are motivating farmers to grow horticulture crops in Kenagarian Sungai Nanam. It can be look from the socio-economic life of farmers who have increased from the previous both in the field of education, health, and housing.